Epoka Soboru Watykańskiego II z perspektywy ks. Andrzeja Bardeckiego - Natalia Radomska (Polonia Sacra)
Vaticanum II was crucial event for Church and change its visage. In the present article are presented opinions upon these events and their participant of priest Andrzej Bardecki. Also historical context of Vaticanum II and its influence on the changes in Church was show.